Chemical and morphological gradient scaffolds to mimic hierarchically complex tissues: From theoretical modeling to their fabrication. Issue 10 (8th May 2016) - Marrella, Alessandra; Aiello, Maurizio; Quarto, Rodolfo; Scaglione, Silvia
ABSTRACT: Porous multiphase scaffolds have been proposed in different tissue engineering applications because of their potential to artificially recreate the heterogeneous structure of hierarchically complex tissues. Recently, graded scaffolds have been also realized, offering a continuum at the interface among different phases for an enhanced structural stability of the scaffold. However, their internal architecture is often obtained empirically and the architectural parameters rarely predetermined. The aim of this work is to offer a theoretical model as tool for the design and fabrication of functional and structural complex graded scaffolds with predicted morphological and chemical features, to overcome the time‐consuming trial and error experimental method. This developed mathematical model uses laws of motions, Stokes equations, and viscosity laws to describe the dependence between centrifugation speed and fiber/particles sedimentation velocity over time, which finally affects the fiber packing, and thus the total porosity of the 3D scaffolds. The efficacy of the theoretical model was tested by realizing engineered graded grafts for osteochondral tissue engineering applications. The procedure, based on combined centrifugation and freeze‐drying technique, was applied on both polycaprolactone (PCL) and collagen‐type‐I (COL) to test the versatility of the entire process. A functional gradient was combined to the morphological one by adding hydroxyapatite (HA) powders, to mimic the bone mineral phase. Results show that 3D bioactive morphologically and chemically graded grafts can be properly designed and realized in agreement with the theoretical model. Biotechnol. Bioeng. 2016;113: 2286–2297. © 2016 Wiley Periodicals, Inc. Abstract : A theoretical model to design and fabricate functional and structural complex graded scaffolds with predicted morphological and chemical features has been developed. The efficacy of the model has been tested by realizing engineered graded grafts for osteochondral tissue engineering applications. The procedure has been applied on both polycaprolactone (PCL) and collagen‐type‐I (COL) and a functional gradient was combined to the morphological one by adding hydroxyapatite (HA) powders, to mimic the bone mineral phase.